Implementasi Komunikasi Orang Tua dan Anak dalam Bidang Pendidikan - Mustafa, Delly (FIkom Unisba, 2006)
In the education world, from primary level to the university, parents role are very dominant in determining their children achievement. The children achivement in family were depended onthe harmony of communication between parents (father and mother) related with children academic achievement. There were some guidelines to raise children in family livelihood. Parents must know the style of parenting in order to properly choose the right way for raising their children.